(untitled) (Baghdad Science Journal, 2019)
The increasing use of antiseptic compounds creates selective pressure cause emergence of antiseptic resistance among Staphylococcus aureus .Resistance mechanism of antiseptic is driven mainly by multi drug resistant (MDR) efflux protein.Sixty five isolates of S.aureuswere collected from different clinical sources and subjected to 11 antibiotics most of them are recognized by efflux systems as extruded substrates. Range of efflux activity was estimated using cartwheel method. Simultaneous discrimination of antiseptic coding genes (qacA/B, smr and norA)as well as nuc and mecA genes among multidrug resistantS.aureus(MRSA) isolates was preformed using multiplex PCR assay , 61 isolatesamong 65 were positive tonucand mecA genes, 58 of them were positive to norA, 14 of them were positive to qacA/B and only two were positive to smr. All isolates detected with qacA/B characterized by fluoroquinolones resistant and most of them show strong efflux activity at cartwheel assay, all of the 14 isolates positive qacA/B were sequenced to differentiate between variants depending on position 323 (aspartic in QacA, alanine in QacB), 3 of them harbored asparagines amino acid at position 323 and considered to be a new variants that reported for the first time.